Management of Sexual Harassment through Assertiveness Skills - SEENA ABRAHAM (Journal of Social Work Education and Practice, 2023)
Objective Assessing and comparing the assertiveness and management of sexual harassment before and after the administration of the assertiveness skills training to the rural adolescent girls. Method Geographical universe of the research is the geographical area of the Kalady Grama Panchayath. The population of the research includes all higher secondary girl students studying in aided schools and government in Kalady Grama Panchayath. The researcher proposes a multi stage sampling system for the research. Research design selected was Quasi –Experimental research design without control group. To collect data the researcher administer the tools like check list to identify the experience of sexual harassment, Questionnaire to assess the management of sexual harassment experiences and a standardized questionnaire to check the assertiveness behaviour among adolescent girls. The collected data was analyzed using appropriate inferential statistical methods employing SPSS 10 version. Findings – Majority of the higher secondary adolescent girls have some form of sexual harassment experiences .The management of these hassasement experiences is also very poor. There is a slight change in the assertiveness level before and after intervention as well as there is change in the management of sexual harassment experience after assertiveness intervention programme. Conclusions – It is clear that poor assertiveness skills lead to problems so it is important for children to give appropriate training to improve these skills. Thus, they can more enjoy their social interactions and feel good about themselves.